2018
DOI: 10.1094/phyto-12-17-0419-r
|View full text |Cite
|
Sign up to set email alerts
|

Causative Role of Grapevine Red Blotch Virus in Red Blotch Disease

Abstract: Grapevine red blotch virus (GRBV) has a monopartite single-stranded DNA genome and is the type species of the genus Grablovirus in the family Geminiviridae. To address the etiological role of GRBV in the recently recognized red blotch disease of grapevine, infectious GRBV clones were engineered from the genome of each of the two previously identified phylogenetic clades for Agrobacterium tumefaciens-mediated inoculations of tissue culture-grown Vitis spp. plants. Following agroinoculation and one or two dorman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 38 publications
4
50
0
2
Order By: Relevance
“…There is now scope with these novel edited materials to assess molecular phenotypes of deranged gene expression, pathogen resistance/tolerance, vector feeding preferences (Zeilinger et al 2018), and GRBV systemic movement by agroinoculations (Yepes et al 2018) on these genome-edited anthocyanin host effector grapevine lines. However, dissolution of the transgenic state or conversion to homozygosity of mutated haplotypes (like TAS4b-2-a2; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now scope with these novel edited materials to assess molecular phenotypes of deranged gene expression, pathogen resistance/tolerance, vector feeding preferences (Zeilinger et al 2018), and GRBV systemic movement by agroinoculations (Yepes et al 2018) on these genome-edited anthocyanin host effector grapevine lines. However, dissolution of the transgenic state or conversion to homozygosity of mutated haplotypes (like TAS4b-2-a2; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The threat of a PD epidemic in northern California and the Pacific Northwest like in southern and central California in the 1880s, 1930s, 1970s, and 1990s remains real. New tools and management strategies are needed to combat grapevine diseases. Despite years of focused efforts by microbiologists, entomologists, and plant physiologist/pathologists, the molecular mechanisms of PD or GRBV disease etiology are not understood (Kyrkou et al 2018;Yepes et al 2018). We hypothesize that Trans-acting small-interfering RNA locus4 (TAS4) (Rajagopalan et al 2006) is a molecular determinant of GRBV and PD host susceptibility.…”
Section: Introductionmentioning
confidence: 98%
“…However, experiments to demonstrate the infectivity of GGVA on the original host, grapevines, have been unsuccessful. Recent research revealed that infectious clones of GRBV could be agroinoculated into tissue cultured grapevine by vacuum-assisted infiltration and reproduced red blotch disease ( Yepes et al, 2018 ). Furthermore, the authors tested whether different cultivars and rootstock genotypes could be infected by GRBV ( Yepes et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research revealed that infectious clones of GRBV could be agroinoculated into tissue cultured grapevine by vacuum-assisted infiltration and reproduced red blotch disease ( Yepes et al, 2018 ). Furthermore, the authors tested whether different cultivars and rootstock genotypes could be infected by GRBV ( Yepes et al, 2018 ). Hence, further experiments to gain important insights into GGVA infection on grapevines are required, possibly using the infectious clone of GGVA on a range of different cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken according to the prescribed methodology of Foundation Plant Services, UC Davis (http://fps.ucdavis.edu). Even though the correlation between the presence of GRBV and appearance of symptoms has been shown to be very high, grapes from tested grapevines (referred to as data vines) were sampled separately within the 120 grapevine pool destined for winemaking to ensure similar chemical compositions. At harvest, 500 berry samples were taken randomly from the lowest, middle and top parts of the clusters from inside and outside of the canopy for each set of RB(−) and RB(+) vines.…”
Section: Methodsmentioning
confidence: 99%